The heirloom [large type] - Lewis, Beverly, 1949- (Lewis, Beverly, 1949- Heritage of Lancaster County, 2023)
"After her widowed father remarries, nineteen-year-old Clara Bender is no longer needed to help run his household. When she comes across letters from her mother's aunt Ella Mae Zook, she sets off to visit Lancaster County's Hickory Hollow to decide where her future lies. The two women form a bond while restoring an heirloom wedding quilt and sharing their lives, with Ella Mae confiding about a tragedy from her courting years. Eventually, Ella Mae suggests Clara stay for the summer, allowing Ella Mae more time with her and giving Clara an opportunity to meet the area's eligible young men. But when the unexpected happens, will Clara find where her heart truly belongs?" --